A micromechanical model for the analysis of multidirectional fiber reinforced polymer laminates. (15th January 2019) - Deng, Xi; Hu, Junfeng; Wang, Wen-Xue; Matsubara, Terutake
Abstract: A new three-dimensional (3D) micromechanical model is proposed to simulate the arbitrary multidirectional carbon fiber reinforced polymer (CFRP) composite laminates. Carbon fiber is assumed as transversely isotropic and linear elastic, matrix is assumed as isotropic and elastic–plastic. Maximum strain criterion is used to describe the failure of fiber and matrix. The stresses, strains and damage are described in the fiber and matrix levels, but the debonding between the fiber and matrix and the delamination between two plies are not modeled in the present analysis. Numerical analyses of nonlinear mechanical behavior of angle-ply [±θ]2s under tension are conducted to verify the validity of the present micromechanical model. Numerical results of nonlinear mechanical behavior, negative Poisson's ratio through the thickness direction, and stress distribution on the free edge show good agreement with previous experimental and analytical results.